(3UaI GdYQT hGdcQSi hJaSjQgeGs - (3CHh eMeO GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdQSj, GdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3bGd Ydi Hf eMeO MOKfi GdMSf Hf GdbGSe Yf GdMSjf Hf GdbGSe bGd SCdJ CHj Yf JChjd eG PcQ Gddg Yfg ef cQSjg hYQTI abGd s
(3BNQgG (B:s
(3hef bGd HPdc ai Gddg abO HQF ef GdeYQhaI HGddg Je s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds